One way to do it is application of series of rules to the expression, just to "teach" Mathematica of how to transform the expression. I will break the chain of transformations into steps to make it better visible. These are your functions: expr1 = (x - x0)^α Sum[a[n] (x - x0)^n, {n, 0, Infinity}] expr2 = D[expr1, x] and here are the results: ![enter image description here][1] Let us do the first transformation: expr3 = expr2 /. u_*\!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]v_\) -> \!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]\((u* v)\)\) this is the result: ![enter image description here][2] The second transformation: expr4 = expr3 /. (x - x0)^m_ \!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]\(s_*\ \*SuperscriptBox[\((x - x0)\), \(q_\)]\)\) -> \!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]\(s*\ \*SuperscriptBox[\((x - x0)\), \(q + m\)]\)\) yielding ![enter image description here][3] and the last one: expr5 = expr4 /. \!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]\(u1_* v_\)\) + \!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]\(u2_* v_\)\) -> \!\( \*UnderoverscriptBox[\(\[Sum]\), \(n = 0\), \(\[Infinity]\)]\(\((u1 + u2)\)*v\)\) gives the result: ![enter image description here][4] [1]: https://i.sstatic.net/bIQk6.gif [2]: https://i.sstatic.net/kqYFl.gif [3]: https://i.sstatic.net/NqDDO.gif [4]: https://i.sstatic.net/e8QkC.gif